2013
DOI: 10.1364/ol.38.002832
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent coupling between localized surface plasmons and excitons in silicon nitride matrix

Abstract: The size-dependent coupling between localized surface plasmons (LSPs) and excitons within a silicon nitride (SiN(x)) matrix is investigated. A strong correlation between the photoluminescence (PL) enhancement and this resonance coupling is observed. From the analysis of the relationship between the dipolar resonance peaks of Ag nanostructures with various sizes and those of PL enhancement, we ascribe the enhancement of PL from the SiN(x) matrix by the addition of Ag nanostructures mainly to the LSP resonance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This happens as a result of optical pumping of the oxide-insulator interface (SiO 2 -Si 3 N 4 ) and insulator trapped charges in Si 3 N 4 triggered by multiple reflections at the interface of each layer on the wafer 20 . The presence of these excitons, well established in literature 19,21 , is validated by capacitance -voltage (C-V) profiling of IS junctions This journal is © The Royal Society of Chemistry 20xx…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…This happens as a result of optical pumping of the oxide-insulator interface (SiO 2 -Si 3 N 4 ) and insulator trapped charges in Si 3 N 4 triggered by multiple reflections at the interface of each layer on the wafer 20 . The presence of these excitons, well established in literature 19,21 , is validated by capacitance -voltage (C-V) profiling of IS junctions This journal is © The Royal Society of Chemistry 20xx…”
mentioning
confidence: 84%
“…More importantly, we show how coupling of excitons and plasmons vary by changing the sizes of gold nanoparticles (AuNPs), while characterizing the pH sensing properties of the surface. When Si 3 N 4 -based IS structures without AuNPs are exposed to white light between 400-800 nm, excitons are generated due to the radiative and non-radiative recombination of electronhole pairs in the Si 3 N 4 top layer 19 . This happens as a result of optical pumping of the oxide-insulator interface (SiO 2 -Si 3 N 4 ) and insulator trapped charges in Si 3 N 4 triggered by multiple reflections at the interface of each layer on the wafer 20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some research works have observed a considerable improvement of the integrated emission intensity from silicon emitting quantum dots (SiQDs) when these are adequately coupled with nanostructured noble metal particles. [25][26][27][28][29][30][31][32][33][34][35] Therefore, the fabrication of coupled silicon-metal nanostructures could be one possible solution for the manufacture of multiple luminescent devices based on silicon. 36 However, it must be emphasized that fabrication processes to make silicon-noble metal coupling structures which show photoluminescence enhancement are not simple.…”
Section: Introductionmentioning
confidence: 99%